Metastrongyloid infection by Aelurostrongylus abstrusus, Troglostrongylus brevior and Angiostrongylus chabaudi in a domestic cat. Issue 11 (September 2015) - Traversa, Donato; Lepri, Elvio; Veronesi, Fabrizia; Paoletti, Barbara; Simonato, Giulia; Diaferia, Manuela; Di Cesare, Angela
Graphical abstract: Highlights: Nematodes affecting the respiratory system of cats have recently received much attention in the scientific community. The lungworm Troglostrongylus brevior of wild felids has recently been described in domestic cats. The heartworm Angiostrongylus chabaudi is an overall little known parasite. This is the first known case of a mixed infection by heartworms and lungworms in a domestic cat. Epidemiological and biological implications of this finding are discussed. Abstract: The "cat lungworm", Aelurostrongylus abstrusus, affects cats worldwide. Recently, other cardio-pulmonary parasites, e.g. Troglostrongylus brevior and Angiostrongylus chabaudi, have been isolated from cats either for the first time or a long time after they were first described. This paper describes the first known mixed infection by A. abstrusus, T. brevior and A. chabaudi in a domestic cat. Biological and epidemiological implications of old and "new" metastrongyloid-caused infections in cats are discussed.